PENGARUH PERENDAMAN (NaOH) TERHADAP KEKUATAN TARIK DAN BENDING BAHAN KOMPOSIT SERAT BAMBU TALI (GIGANTOCHLOA APUS) BERMATRIKS POLYESTER - Kosjoko, Kosjoko (Universitas Lambung Mangkurat, 2014)
Effect of Immersion (NaOH) bamboo fiber rope (Gigantochloa smear) for 120 minutes and the use of one-way fiber can be a problem for maximum improvement in mechanical properties of bamboo fiber composite straps. The purpose of the research, manufacture of composites made from polyester matrix reinforced with fibers type157BTQN natural bamboo, with a 5% NaOH immersion treatment, per 1 liter of distilled water for 120 minutes, to determine the mechanical properties of the composite tensile strength and bending strength with the variation of fiber volume fraction 20 %, 30%, and 40%.The method is done by arranging a one-way natural fiber bamboo fiber with polyester matrix type 157 BTQN with variation of fiber volume fraction of 20%, 30%, and 40%. Hardener used is MEKPO with a concentration of 5% NaOH. Composites are made by hand lay-up method. The main variable is the study of variation of fiber volume fraction of 20%, 30%, and 40%, with 5 grams of soaking treatments per 1 liter of distilled water NaOH for 120 minutes. Specimens and tensile and bending test procedures refer to standard ASTM D 638-03 and ASTM 790-03.The results of this study indicate that the addition of fiber volume fraction of 20%, 30%, 40% and 5% NaOH immersion treatment, per 1 liter of distilled water may increase the interfacial adhesion between the fiber and matrix. The highest tensile strength at 5% NaOH immersion treatment for 120 minutes of natural bamboo fiber composite with 40% volume fraction of 42 kN/mm2, for NaOH and without treatment with 40% volume fraction of 13 kN/mm2. While the highest Bending strength of bamboo fiber composite immersion in 5% NaOH treatment for 120 minutes with 40% volume fraction of 15.4 kN/mm2, for 40% volume fraction of 5.7 kN/mm2 without treatment.Â Keywords: bamboo fiber rope (Gigantochloa lear), NaOH, polyester, tensile strength and bending strength.